Answer:
A
Explanation:
Given
x³ +x ² - 6x ( to find the zeros equate to zero ), that is
x³ + x² - 6x = 0 ← factor out x from each term
x(x² + x - 6) = 0
To factorise the quadratic
Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (+ 1)
The factors are + 3 and - 2, since
3 × - 2 = - 6 and 3 - 2 = + 1, hence
x(x + 3)(x - 2) = 0
Equate each factor to zero and solve for x
x = 0
x + 3 = 0 ⇒ x = - 3
x - 2 = 0 ⇒ x = 2
The zeros are x = - 3, x = 0, x = 2 → A